The unlucky seven : a Gil Yates private investigator novel - Boyle, Alistair (Santa Barbara, CA : A.A. Knoll, 1997)
Private investigator Gil Yates must solve the mystery of who is sending letter bombs to seven of the most influential and wealthy men in the world.
Booklist.
Library Journal.
Publisher's Weekly.
Adult
Keywords: Private investigators -- California -- Fiction; Yates, Gil (Fictitious character) -- Fiction; Mystery fiction; Private investigators -- Fiction; Yates, Gil (Fictional character) -- Fiction; California -- Fiction; California -- Fiction; Detective and mystery stories